ANALISIS DAN PERANCANGAN SISTEM INFORMASI ADMINISTRASI ARSIP BERBASIS WEB PADA KANTOR BIRO PBMD SETDA PROVINSI JAMBI - Madhrozji, Tutuk; Effiyaldi, Effiyaldi (LPPM Universitas Dinamika Bangsa, 2019)
Now in making administration archive a letter the office management bureau goods belonging to a regionsetda jambi there are several obstacles such as the preparation of reports on administration archiveespecially when will seen reports in accordance the period desired, Search document have been storedwhen are still difficult to and long because have to open the documents old and look for one by one andoften difficulty when will make copy the last on the period required, Hence writer provide solutions ofdesign administration archive information system to ease employees in process administrative dataarchives and ease in for finding data and the report, In this research researchers used tool uml ( the unifiedmodeling language ) and models the prototype.Where expected outcomes be design a system that canmake searching system faster and preparing reports more easily and fast.